Retinal Occlusive Vasculitis in a Patient with Hyperimmunoglobulin E Syndrome - Mohsen Farvardin; Mohammad Hassan Jalalpour; Mohammad Reza Khalili; Golnoush Mahmoudinezhad; Fereshteh Mosavat; Soheila Aleyasin; Hamidreza Jahanbani-Ardakani (Case Reports in Ophthalmological Medicine)
Background. Hyperimmunoglobulin E syndrome (HIES), or Job’s syndrome, is a primary immunodeficiency disorder that is characterized by an elevated level of IgE with values reaching over 2000 IU (normal<200 IU), eczema, and recurrent staphylococcus infection. Affected individuals are predisposed to infection, autoimmunity, and inflammation. Herein, we report a case of HIES with clinical findings of retinal occlusive vasculitis. Case Presentation. A 10-year-old boy with a known case of hyperimmunoglobulin E syndrome had exhibited loss of vision and bilateral dilated fixed pupil. Fundoscopic examination revealed peripheral retinal hemorrhaging, vascular sheathing around the retinal arteries and veins, and vascular occlusion in both eyes. A fluorescein angiography of the right eye showed hyper- and hypofluorescence in the macula and hypofluorescence in the periphery of the retina, peripheral arterial narrowing, and arterial occlusion. A fluorescein angiography of the left eye showed hyper- and hypofluorescence in the supranasal area of the optic disc. Macular optical coherence tomography of the right eye showed inner and outer retinal layer distortion. A genetic study was performed that confirmed mutations of the dedicator of cytokinesis 8 (DOCK 8). HSV polymerase chain reaction testing on aqueous humor and vitreous was negative, and finally, the patient was diagnosed with retinal occlusive vasculitis. Conclusion. Occlusive retinal vasculitis should be considered as a differential diagnosis in patients with hyperimmunoglobulin E syndrome presenting with visual loss.